Kontruksi Budaya Literasi Guru dan Siswa dengan CERIA di MIN 4 Sragen - Rohmawati, Rohmawati (Allimna: Jurnal Pendidikan Profesi Guru, 2024)
The purpose of this scientific work is to find out the culture of literacy that exists at MIN 4 Sragen. How is the application of literacy with CERIA in its daily implementation. What is the meaning of CERIA, literacy culture, the results of the literacy culture of teachers and students with CERIA at MIN 4 Sragen.  This research method uses a type of qualitative research, which is research that aims to gain understanding and understanding of the literacy culture at MIN 4 Sragen. This research includes descriptive research, because it aims to describe certain characteristics, trying to explain and interpret literacy activities at MIN 4 Sragen. The literacy culture at MIN 4 Sragen with CERIA is implemented by teachers and students. All madrasah residents carry out literacy activities both outside the classroom and in the learning process. There are four literacies included in the learning process, namely reading, science, numeracy and socio-cultural literacy. The results of this scientific work conclude that the culture of literacy at MIN 4 Sragen by telling stories through SBC activities, innovative learning by linking learning and four literacies and giving appreciation by publishing books. The results achieved by literacy culture at MIN 4 Sragen are students love to read, are able to understand reading texts, are able to tell stories, recognize various types of literacy and publish books.